A Look at Digital Transformation: Can Society Be Persuaded To a New Authentication Method – Behavioral Biometrics? - Krzysztoń, Emanuel (Bobcatsss, 2023)
The 21st century brings many technological novelties and modifications to existing solutions. The digital transformation that we undergo in every aspect of life often affects us against our will, with varying results. Thousands of years ago, when a human rubbed two stones together, he caused a spark that started a chemical phenomenon, but above all - a revolution. Today, lighting a bonfire does not arouse great emotions, we are faced with many other technological novelties aimed at making our lives easier. In the past, when human didn’t need the fire, he had a choice. The present shows that we are becoming strongly dependent on technology and our choice becomes very limited or impossible. As a result, we agree to the terms offered. It is worth to investigate whether we take a bold decision overnight? What guides us in making such key decisions in our lives? The main goal of this paper is to take a look at safeguards used to protect our goods, in information technology. Until now, the security measures used to authenticate the user were in the form of i.a. login and passwords, two-factor authentication (2FA), universal 2nd Factor (U2F), biometrics. Each of these solutions has its advantages and disadvantages. It would seem that these are the best solutions, and using them together would provide a multi-layer security. However, does it not become a significant obstacle in everyday use? Then behavioral biometrics comes to the rescue, which aims to learn our behaviour using machine learning and to clearly confirm in real time whether the person using the service or device is the owner. Using this method, many doubts and concerns arise about the technology itself. Based on the available research, literature and other sources, I will look for answers to the question „Can the public be persuaded to use this method of authentication?”. Justifying the reply, I will analyse the available tools and refer to the document of General Data Protection Regulation.